Increasing recognition of historically marginalized scientists: Lessons learned from the Nomination Task Force - Keesee, Amy M.; Claudepierre, Seth G.; Bashir, M. Fraz; Hartinger, Michael D.; MacDonald, Elizabeth A.; Jaynes, Allison N. (Frontiers in Astronomy and Space Sciences, 2022)
The Space Physics and Aeronomy (SPA) Section of the American Geophysical Union (AGU) created a Nomination Task Force (NTF) in 2017 upon concerns that the numbers of women nominated for AGU Fellow were significantly lower than would be expected based on SPA membership representation, including as low as zero in two of the four preceding years. Now that the NTF has been in existence through four cycles of AGU Honors and Awards, the outcomes indicate the success of the NTF in increasing the number of nominations for scientists from historically marginalized groups. These data indicate that the work of the NTF has enhanced the nomination pool rather than occurring at the expense of other nominees. Until recently, the ability to collect and distribute demographic information has been limited, and cisgender binary identities are often inferred. Moving forward it is a goal of AGU to be more inclusive and intentional with respect to gender, racial, and ethnic identities. We share our best practices and success stories with a broad audience to help others build upon the work of the NTF within their own institutions and professional groups. We also discuss challenges that we are still facing and provide suggestions for continuing to improve the process.